Plasma Amino Acid Abnormalities in Chronic Heart Failure. Mechanisms, Potential Risks and Targets in Human Myocardium Metabolism - Roberto Aquilani (Nutrients, 2017)
The goal of this study was to measure arterial amino acid levels in patients with chronic heart failure (CHF), and relate them to left ventricular function and disease severity. Amino acids (AAs) play a crucial role for heart protein-energy metabolism. In heart failure, arterial AAs, which are the major determinant of AA uptake by the myocardium, are rarely measured. Forty-one subjects with clinically stable CHF (New York Heart Association (NYHA) class II to IV) were analyzed. After overnight fasting, blood samples from the radial artery were taken to measure AA concentrations. Calorie (KcalI), protein-, fat-, carbohydrate-intake, resting energy expenditure (REE), total daily energy expenditure (REE × 1.3), and cardiac right catheterization variables were all measured. Eight matched controls were compared for all measurements, with the exception of cardiac catheterization. Compared with controls, CHF patients had reduced arterial AA levels, of which both their number and reduced rates are related to Heart Failure (HF) severity. Arterial aspartic acid correlated with stroke volume index (r = 0.6263; p < 0.0001) and cardiac index (r = 0.4243; p = 0.0028). The value of arterial aspartic acid (µmol/L) multiplied by the cardiac index was associated with left ventricular ejection fraction (r = 0.3765; p = 0.0076). All NYHA groups had adequate protein intake (≥1.1 g/kg/day) and inadequate calorie intake (KcalI < REE × 1.3) was found only in class IV patients. This study showed that CHF patients had reduced arterial AA levels directly related to clinical disease severity and left ventricular dysfunction.